DESIGNING OF A DIGITAL VIDEO FOR BASIC ENGLISH TEACHING TO MIGRANT MAID CANDIDATES FROM EAST NUSA TENGGARA PROVINCE - Nusi, Jacob; Metboki, Yakob; Marpaung, Tiarma (Journal of Language, Education, Literature, and Culture, 2023)
This paper describes the design of a digital video for prospective migrant maids in Kupang, Eastern Indonesia. The study answers the problem of what is the design process of a digital video for migrant maid candidates to learn Basic English. It aims to elucidate the design of a digital video for teaching Basic English. The study applied a descriptive qualitative approach. The study participant was a tutor at an official training center for migrant maid candidates in Kupang, East Nusa Tenggara province of Indonesia. The research instruments are documentation and interviews. The design of the video comprises needs analysis, design, preliminary evaluation, Development and evaluation, and final Development. Analysis of the data applied descriptive qualitative research. Data for the analysis is derived from every phase of the design video process. The study's findings reveal that the study is based on the needs analysis results of Basic English teaching in the context. The design video process involves related key parties among the tutor, an English lecturer, and a vocational school student. The evaluation results, namely content, layout, language, and writing mechanics, serve as underlying references for video design. The Development of the video design carries out a multilingual video composed of Indonesian language, English, and Cantonese. Moreover, the present study also reveals that English tutors need more multilingual content videos in English to teach Basic English to migrant maid candidates from East Nusa Tenggara.